SURAT AR-RUUM AYAT 21 PETUNJUK TUHAN UNTUK MENJALANKAN NILAI-NILAI PENDIDIKAN DALAM KELUARGA - Ridwan Ridwan; Ridha Romdiyani; Arfi Hilmiati; Muhammad Husni Abdulah Pakarti (USRAH: Jurnal Hukum Keluarga Islam, 2022)
In Islamic teachings, marriage is the only legal way to channel lust between men and women, in the sense that marriage is the only legal and recognized way to create love between the two. The purpose of this study was to describe the values of marriage education according to Al-Quran Surat ar-Ruum verse 21. This search included a literature search, namely. H. research that collects information and knowledge by using various materials in the bibliography. (Book). By using an analytical descriptive approach, look for facts, findings and ideas from thoughts by analyzing, interpreting and generalizing research results. This study uses primary data as the main source and secondary data sources as supporting data sources. The data analysis method adopts a data analysis method in which the collected data is analyzed, namely an analysis that aims to reveal ideas about the values of Islamic marriage education according to surah ar-Ruum verse 21 of the Qur'an. The results of the study show that the values of Islamic marriage education are according to the Al-Quran-Surah ar-Ruum verse 21, this verse describes Sakina, Mawadda and Rahma. Sakinah means peace, serenity, security or serenity. Mawaddah is al-jima' (intercourse). Even though Rahma is a love that cares more about those she loves than herself, Sakina embodies the values of Islamic education: Fathonah, Amanah, Shiddiq, Tabligh and Qonaah. The values of Islamic education contained in Mawaddah include: Ikhlas, al-Riyadat, Tasamuh, Muhasabah. The values of Islamic education contained in Rahmah: ta'aruf, tafahum and takaful, benefactors.